Ulcerated Hemangioma - Surveillance Only - Chiriac Anca; Chiriac Anca Eduard; Pinteala Tudor; Foia Liliana; Brzezinski Piotr (Folia Medica, 2015)
Infantile hemangiomas are reported in 10-12% of children less than 1 year of age, with ulceration in about 5-13% of cases. Little is known about the mechanism of this disease and explanations are still being looked for.